MEWUJUDKAN SEKOLAH BERBASIS LINGKUNGAN SEHAT MELALUI PEMBENTUKAN DAN PEMBERDAYAAN TIM JURU PEMANTAU JENTIK DI SMPN 5 KOTA PADANG - Masrizal Masrizal; Yudi Yudi; Mahesa Mahesa (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Schools function as places of learning and become a threat of disease transmission if they are not managed properly. School-age for children is also a time of vulnerability to various diseases, such as diarrhea, infectious diseases, dengue fever, etc. In addition, school-age is also the most appropriate time to instill understanding, healthy living habits. They respond to this problem, the formation and empowerment of the larva monitoring team at SMPN 05 Padang City. Based on the author's observations, SMPN 05 Padang City has water storage facilities, is very vulnerable to causing various disease transmission agents attacking students at school. Through the formation, the empowerment of the larva monitoring team is expected to be a driving force in creating a clean and healthy environment at school and where they live. The larva monitoring team consists of students who meet the criteria and have been trained to participate in carrying out some efforts to maintain and improve environmental health in schools. This service activity will begin with socialization and counseling activities from the service team, after that the recruitment and formation of a larva monitoring team is carried out, the next stage, the appointed team can carry out the movements that must be carried out, including larva monitoring, the Mosquito Nest Eradication Movement, and finally carried out recording and reporting. In contrast, in the evaluation stage, an assessment of the development of attitudes and behavior of SMPN 05 Padang City students is carried out towards the school larvae monitoring team. Through the larva monitoring team, which is the motor of the environmental health care movement, schools are expected to implement and teach other students to promote healthy schools that are free from various diseases.